How do patient and practitioner characteristics influence empathy in healthcare? Protocol for a systematic review and meta-analysis - Kamlesh Khunti; Jeremy Howick; Clare Gillies; Keith Nockels; Karin Meissner; Cleo Laura White; Dinesh Palipana; Cathy Harrell (BMJ Open)
Introduction Empathy is a core component of high-quality care yet is expressed and received in different ways depending on the characteristics (including gender, race, socioeconomic status and disability) of both practitioners and patients. However, the evidence exploring how these characteristics or their overlap (‘intersectionality’) influence empathy has not been synthesised.Methods and analysis We will systematically review and meta-analyse studies exploring the influence of healthcare practitioners and patient characteristics on empathy in healthcare. MEDLINE, EMBASE (via Scopus), Scopus, PsycINFO, CINAHL, CENTRAL Web of Science, Cochrane Database of Systematic Reviews and Database of Abstracts of Reviews of Effects will be searched from database inception to present. Reference chasing will be used to identify additional studies. Studies that report empathy levels using either (1) the patient-reported Consultation and Relational Empathy Measure or (2) the practitioner or student-reported Jefferson Scale of Empathy. This will include validated versions or translations of both scales.Two reviewers will independently screen titles, abstracts, and full texts and extract data using Rayyan. Discrepancies will be resolved in discussion with a third author if necessary. Two independent authors will evaluate the risk of bias using the Joanna Briggs Institute tools.Continuous data will be analysed based on the mean, SD, sample size and 95% CIs. Sensitivity analyses will be used to explore the potential impact of risk of bias and use of imputed data. We will explore differences between countries, demographic characteristics, disciplines and lengths of time in practice experience, as well as differences over time (comparing more recent with older studies). We will also explore differences between patient-reported and practitioner-reported empathy.We will report our findings following the Preferred Reporting Items for Systematic reviews and Meta-Analyses guidelines and flowchart.Ethics and dissemination Ethical approval is not required for this review as primary data will not be collected. The review will be disseminated through peer-reviewed publication and presented at conferences.PROSPERO registration number CRD42024604677.